2011
DOI: 10.1016/j.cub.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A Secreted Protein Promotes Cleavage Furrow Maturation during Cytokinesis

Abstract: Summary Developmental modifications in cell shape depend on dynamic interactions between the extracellular matrix and cytoskeleton. In contrast, existing models of cytokinesis describe substantial cell surface remodeling that involves many intracellular regulatory and structural proteins but includes no contribution from the extracellular matrix [1–3]. Here, we show that extracellular hemicentins assemble at the cleavage furrow of dividing cells in the C. elegans germline and in preimplantation mouse embryos. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 26 publications
6
74
3
Order By: Relevance
“…A recent study showed that a secreted extracellular matrix protein, hemicentin, regulates cytokinesis (Xu and Vogel, 2011), giving an example of the notion that a secreted ligand and its receptor-mediated signaling is involved in cytokinesis. Therefore, the present data may give another example of the involvement of secreted ligand-activated signaling in cytokinesis.…”
Section: Similar Spatial Localization Of Fz2 and Chmp4b At The Midbodymentioning
confidence: 99%
“…A recent study showed that a secreted extracellular matrix protein, hemicentin, regulates cytokinesis (Xu and Vogel, 2011), giving an example of the notion that a secreted ligand and its receptor-mediated signaling is involved in cytokinesis. Therefore, the present data may give another example of the involvement of secreted ligand-activated signaling in cytokinesis.…”
Section: Similar Spatial Localization Of Fz2 and Chmp4b At The Midbodymentioning
confidence: 99%
“…Completion of cytokinesis is coupled to the secretory pathway, which provides new cell membrane and proteins of the extracellular matrix (ECM) (Xu and Vogel, 2011). When cells have defects in secretion of ECM, contractile rings can retract before completion, resulting in multinucleate cells (Xu and Vogel, 2011). Yeast cells assemble an extracellular septum that primarily comprises β-Dglucan and α-D-glucan polymers (Cortes et al, 2012;Humbel et al, 2001) that is essential for the contractile ring constriction (Arasada and Pollard, 2014;Liu et al, 1999;Proctor et al, 2012;Sipiczki and Bozsik, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Completion of cytokinesis is coupled to the secretory pathway, which provides new cell membrane and proteins of the extracellular matrix (ECM) (Xu and Vogel, 2011). When cells have defects in secretion of ECM, contractile rings can retract before completion, resulting in multinucleate cells (Xu and Vogel, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the extracellular matrix is not a rigid structure and does not provide osmotic support, it is considered the functional equivalent of the cell wall, and both structures are essential for the cell (2)(3)(4)(5). In addition, as in fungal cells, some extracellular matrix polymers are also important for cytokinesis (6)(7)(8)(9).…”
mentioning
confidence: 99%